Mapping the Terrain for Pathogen Persistence and Proliferation in Non-potable Reuse Distribution Systems: Interactive Effects of Biofiltration, Disinfection, and Water Age - Ghosh, Sudeshna; Zhu, Ni Joyce; Milligan, Erin; Falkinham, Joseph O; Pruden, Amy; Edwards, Marc A (Environmental science & technology, 2021)
Diverse pathogens can potentially persist and proliferate in reclaimed water distribution systems (RWDSs). The goal of this study was to evaluate interactive effects of reclaimed water treatments and water age on persistence and proliferation of multiple fecal (e.g., Klebsiella, Enterobacter) and non-fecal (e.g., Legionella, mycobacteria) gene markers in RWDSs. Six laboratory-scale RWDSs were operated in parallel receiving the influent with or without biologically active carbon (BAC) filtration + chlorination, chloramination, or no disinfectant residual. After 3 years of operation, the RWDSs were subject to sacrificial sampling and shotgun metagenomic sequencing. We developed an in-house metagenome-derived pathogen quantification pipeline, validated by quantitative polymerase chain reaction and mock community analysis, to estimate changes in abundance of ∼30 genera containing waterborne pathogens. Microbial community composition in the RWDS bulk water, biofilm, and sediments was clearly shaped by BAC filtration, disinfectant conditions, and water age. Key commonalities were noted in the ecological niches occupied by fecal pathogen markers in the RWDSs, while non-fecal pathogen markers were more varied in their distribution. BAC-filtration + chlorine was found to most effectively control the widest range of target genera. However, filtration alone or chlorine secondary disinfection alone resulted in proliferation of some of these genera containing waterborne pathogens.